A case‐control study of the association between sialolithiasis and osteoporosis. (28th February 2019) - Hung, Shih‐Han; Xirasagar, Sudha; Cheng, Yen‐Fu; Lin, Herng‐Ching
Abstract : Objective: The purpose of this study was to evaluate the association between osteoporosis and salivary gland stone using a population‐based claims database. Design: A case‐control design. Setting: Taiwan. Participants: We retrieved the sample for this case‐control study from the Taiwan "Longitudinal Health Insurance Database 2005." All 557 patients aged 40 years or older with a diagnosis of sialolithiasis were cases, and 1671 matched controls (without sialolithiasis) were selected. Subjects and Methods: We used the chi‐square test to explore differences between cases and controls on socio‐demographic characteristics. Furthermore, conditional logistic regressions were used to examine the association of sialolithiasis with previously diagnosed osteoporosis. Results: Of 2228 sampled patients, 171 (7.68%) had ever been previously diagnosed with osteoporosis; 58 (10.41%) among cases and 113 (6.76%) among controls ( P = 0.005). Conditional logistic regression analysis found that the odds ratio (OR) of prior osteoporosis for cases was 1.79 (95% confidence interval [CI]: 1.24‐2.59, P = 0.002) relative to controls after adjusting for urbanisation and the selected medical co‐morbidities. Furthermore, we found that among patients aged ≥65 years, the adjusted OR of prior osteoporosis for cases was 1.89 (95% CI = 1.02‐3.51). No significant relationship was observed among patients aged <65 years old. Conclusion: This study demonstrates an association between sialolithiasis and osteoporosis. Although the finding warrants further investigation, the results call for more awareness of the possible concurrence of osteoporosis among physicians and patients with salivary gland stones.